Electroneutral polymersomes for combined cancer chemotherapy. (15th October 2018) - Aibani, Noorjahan; Nesbitt, Heather; Marino, Nino; Jurek, Joanna; O'Neill, Caolin; Martin, Chloe; Di Bari, Ivana; Sheng, Yingjie; Logan, Kieran; Hawthorne, Susan; McHale, Anthony; Callan, John F.; et al.
Graphical abstract: Abstract: Combination cancer chemotherapy provides an important treatment tool, both as an adjuvant and neoadjuvant treatment, this shift in focus from mono to combination therapies has led to increased interest in drug delivery systems (DDS). DDSs, such as polymersomes, are capable of encapsulating large amounts of multiple drugs with both hydrophilic and hydrophobic properties simultaneously, as well as offering a mechanism to combat multi drug resistant cancers and poor patient tolerance of the cytotoxic compounds utilised. In this article, we report the formulation and evaluation of a novel electroneutral polymersome capable of high encapsulation efficacies for multiple drugs (Doxorubicin, 5-Fluorouracil and leucovorin). The in-vivo biodistribution of the polymersome were established and they were found to accumulate largely in tumour tissue. Polymersome encapsulating the three chemotherapeutic drugs were assessed both in-vitro (BxPC-3 cell line) and in-vivo (following intratumoral and intravenous administration) and compared with the same concentration of the three drugs in solution. We report better efficacy and higher maximum tolerated dose for our combination drug loaded polymersomes in all experiments. Furthermore, intratumorally injected combination drug loaded polymersomes exhibited a 62% reduction in tumour volume after 13 days when compared with the free combination solutions. A smaller differential of 13% was observed for when treatment was administered intravenously however, importantly less cardiotoxicity was displayed from the polymersomal DDS. In this study, expression of a number of survival-relevant genes in tumours treated with the free chemotherapy combination was compared with expression of those genes in tumours treated with the polymersomes harbouring those drugs and the significance of findings is discussed. Statement of significance: The shift in focus from mono to combination chemotherapies has led to an increased interest in the role of drug delivery systems (DDS). Liposomes, although commercialized for mono therapy, have lower loading capacities and stability than their polymeric counterpart, polymersomes. Polymersomes are growing in prevalence as their advantageous properties are better understood and exploited. Here we present a novel polymersome for the encapsulation of three anticancer compounds. This is the first time this particular polymersome has been used to encapsulate these three compounds with both an in-vitro and in-vivo evaluation carried out. This work will be of interest to those in the field of combination therapy, drug delivery, drug toxicity, multidrug resistance, liposomes, DDS and polymersomes.